Exploring the Issues Faced by Self Financing Teaching Faculty: A Nano-Topological Analysis - R.Mohanapriya; M.Nagarathinam (Utilitas Mathematica, 2025)
In recent years self financing teaching faculty have faced numerous challenges, including inadequate salaries, lack of respect from management, and a poor working atmosphere. These issues have significantly impacted the well being and productivity of educators. This paper seeks to explore and evaluate these common challenges by applying the concept of nano topo- logical space. Through this novel framework, we aim to provide a unique perspective on the intersection of workplace dynamics and individual faculty experiences at the microlevel. By analyzing the systemic and relational structures within the academic environment we aim to highlight the intricacies of these problems and suggest potential solutions for improving the situation of selffinancing teaching staff.